Eggshell catalyst assisted palm biodiesel production for blending of B10 blended diesel fuel - Abdul Patar, Mohd Affifudin (2020)
Palm biodiesel is currently being internationally debated, more so in Malaysia. The study of this field is increasing day by day in finding ways to reduce its production cost. This study was conducted to analyze the trend of different calcination temperatures to the production of calcium oxide catalyst derived from waste eggshells. The temperatures used are 900°C, 920°C and 950°C. Three different samples of CaO powders were then tested with SEM for surface morphology, XRD for phase present in powders and FTIR to determine presence of bands. The best catalyst is selected to assist the palm biodiesel production through transesterification method. The transesterification method consists of varying parameters of molar ratios (9:1, 12:1 and 15:1) and catalyst content (2%, 3% and 4%), with fixed parameters of 65°C reaction temperature and 600rpm stirring speed. Nine samples were made, and each sample were tested for their physical properties in accordance to the ASTM D6751 standard. The best sample was produced in bulk and blended into EB10 (10% bio-content diesel). The biodiesel blend was also tested for its properties which includes water content, kinematic viscosity, flash point, density and ester content. Lastly, the blended diesel EB10 is compared to a local station B10 diesel blend for its physical properties. It is found that calcination temperature of 920°C is determined to be the most optimum as it gives out the higher yield of calcium oxide while using less energy consumption. For transesterification, parameters with 12:1 molar ratio, 4 wt.% catalyst content are deemed to be the most optimum which yielded 98.89% of biodiesel. This blended diesel blend EB10 was also tested for its properties and found out that it is safe to be applied daily. The blend was also compared to the quality of market available petroleum diesel from a local petrol station and found to have the same quality to it. As for recommendations, further research by using higher blends of biodiesel (B15 or higher) should be study with the same eggshell catalyst synthesized.